Occurrence of Occult Malignancies in Reduction Mammoplasties - Waldner, Matthias; Klein, Holger J.; Künzi, Walter; Guggenheim, Merlin; Plock, Jan A.; Giovanoli, Pietro (Frontiers in Surgery, 2018)
Objectives: Patients undergoing reduction mammoplasty (RM) bear the risk of having occult breast cancer nests. The detection rate of malignant neoplasms in the resected specimens, varies greatly in the literature. The aim of our present study was to analyze risk factors and evaluate histopathological findings in our cohort of patients who underwent RM towards our center. Material and methods: In this retrospective single center study we analyzed 559 female patients (median age 35.99 (±13.34)) who underwent RM between 2000 and 2010. The presence of carcinoma and ductal- (DCIS) or lobular carcinoma in situ (LCIS) were considered as pathological findings. Body mass index (BMI), age, surgical technique and mass of resected tissue were included into the analysis. Results: There were 6 cases of occult neoplasia (1.08 %) including 2 cases of breast cancer, one multicentric DCIS and 3 cases of LCIS (0.54 %) in 559 patients. Patients with breast cancer showed a significant increased median age: 49y median (IQR ±18) vs. 35y (IQR ±21) (p=0.004) and a trend towards increased BMI: 25.88 median (IQR ±7.3) vs. 24.50 (IQR ±4.09) (p=0.219), compared to patients without pathological results. One patient with occult carcinoma had a negative preoperative mammography, a patient with LCIS a negative preoperative breast ultrasound. Conclusions: In our study the occurrence of occult neoplasia was associated with increased age and showed a trend towards increased BMI when compared to patients without pathological findings. The study demonstrates the necessity of thorough medical history, preoperative diagnostic screening and histopathological analysis of all resected specimens.